Opportunities in rooftop greenhouses in Stockholm - Sen, Felicia (2018)
Due to climate change, our resource depleation, population growth and further, our reliance on the world’s food production creates vulnerabilities and we need to find alternative agriculture methods. Commercial rooftop greenhouses are developing all around the world and to Stockholm this create an opportunity to produce food all year. The aim of this thesis was to explore the potentials of commercial rooftop greenhouse urban agriculture in the city of Stockholm. Three methods were combined consisting of a qualitative and quantitative approach. Four companies that practice urban agriculture was studied, Bee Urban, Coop, Grönska and Plantagon. The results indicated that 490 roofs had potential and where 114 among these were better suited for a greenhouse. The combined methods approach showed that the areas Enskede-Årsta-Vantör, Bromma, Hägersten-Liljeholmen, Skärholmen, Rinkeby-Kista, Östermalm and Kungsholmen had better potential for larger operations considering the buildings and the industrial areas where most of these were placed in. Industrial symbioses, larger operations and a low-cost strategy was further identified to be better used in these areas. Södermalm and Spånga-Tensta had least potential for a rooftop greenhouse and were better suited for smaller operations if implementing one e.g. using a community supported agriculture business model. Finally, this thesis shows where and how a potential commercial rooftop greenhouse can be implemented and operated in the city of Stockholm. Further on, it suggests an alternative way of agriculture and to minimize our impact on the environment and how we can work to foster a sustainable development and a sustainable urban planning.